How policymakers should deal with the delayed benefits of early childhood programs - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2009)
This chapter is a draft of Chapter 7 of a planned book, Preschool and Jobs: Human Development as Economic Development, and Vice Versa. This book analyzes early childhood programs' effects on regional economic development. Four early childhood programs are considered: 1) universally accessible preschool for four-year-olds of similar quality to the Chicago Child Parent Center program; 2) the Abecedarian program, which provides disadvantaged children with high-quality child care and preschool from infancy to age five; 3) the Nurse Family Partnership, which provides low-income first-time mothers with nurse home visitors from the prenatal period until the child is age two; and 4) the Parent Child-Home program, which provides home visits and educational toys and books to disadvantaged families when the child is between the ages of 2 and 3. The book considers the main benefit of state economic development to be the resulting increase in earnings of the original residents who stay in that state. Early childhood programs increase residents' earnings largely by increasing the quantity and quality of local labor supply. These programs will increase the employability and wages of former child participants in these programs. The book compares the effects on local earnings of early childhood programs with the effects of business incentives (e.g., property tax abatements). Business incentives increase local residents' earnings by increasing the quantity and/or quality of local labor demand. This chapter considers a problem with early childhood programs: their effects on earnings are mostly long-delayed. The delay occurs because most earnings effects are on former child participants. The chapter considers appropriate discounting of benefits. The chapter considers how the upfront costs of early childhood programs can be delayed or reduced. The chapter considers how the long-run benefits of early childhood programs can be moved up or increased.
Keywords: J13; J24; I21; R23; R31; R30; 330